Faktor-Faktor Yang Mempengaruhi Kejadian Carpal Tunnel Syndrome (CTS) Pada Petani Penyadap Karet: Studi Cross-Sectional Di Desa Tuindrao Satu, Kabupaten Nias Selatan - Ideluonsius Indra Parasian Purba; Santy Deasy Siregar; Hartono Hartono (STIKES Columbia Asia Medan, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a compression neuropathy of the median nerve at the wrist, commonly associated with repetitive occupational activities. Rubber farmers represent a high-risk group due to the continuous, repetitive hand motions involved in rubber tapping. Objective: To analyze factors associated with CTS among rubber farmers in Tuindrao Satu Village, South Nias Regency. Methods: A cross-sectional study was conducted in March 2026. The total population of 53 rubber farmers was recruited, yielding 38 respondents via total sampling. Data were collected through structured interviews, questionnaires, and anthropometric measurements. Bivariate analysis was performed using the Chi-Square test at a 95% confidence level (α = 0.05). Results: The prevalence of CTS history was 65.8% (n = 25). Repetitive motion was the sole factor significantly associated with CTS incidence (p = 0.044). Age (p = 0.222), body mass index (p = 0.362), awkward hand posture (p = 0.122), and ergonomic working position (p = 0.576) showed no significant associations. Conclusions: Repetitive motion during rubber tapping is the primary occupational risk factor for CTS in this population. Targeted ergonomic interventions, including scheduled rest breaks and stretching exercises, are recommended to mitigate CTS risk among informal agricultural workers.